PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF DAN DISCOVERY LEARNING DI SEKOLAH DASAR - Nayla Widi Fatiha (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
Teaching models are a key component in determining the success of the educational process in primary schools. The selection of an appropriate teaching model will influence the level of student activity and learning outcomes. Two models widely applied in primary school education are the cooperative learning model and discovery learning. Both models are oriented towards student-centred learning, yet they possess distinct characteristics and approaches within the learning process. This article aims to analyse and compare the cooperative learning model and discovery learning in enhancing student activity and learning outcomes in primary schools. The method used is a literature review, examining various sources of literature including books, scientific journals, and educational policy documents. The analysis was conducted using a descriptive-comparative approach to identify the similarities, differences, and strengths of each model. The findings indicate that the cooperative learning model is more effective in enhancing students’ social skills, cooperation, and active participation through group discussions. Meanwhile, discovery learning is more effective in developing critical and analytical thinking skills, as well as a deep conceptual understanding through the discovery process.